Dependence of the optical properties on the substrate temperature in ZnO thin films grown on flexible polyimide substrates - Leem, Jae Hyeon; Son, Dong Ick; Kim, Su Youn; Kim, Tae Whan; Choi, Won Kock (KOREAN PHYSICAL SOC, 2008)
The optical properties of ZnO thin films grown on flexible polyimide (PI) substrates at various temperatures were investigated. X-ray diffraction patterns showed that the ZnO thin films grown on PI substrates had a c-axis preferential orientation. Photoluminescence (PL) spectra showed that the peaks at 3.32 and 3.36 eV could be attributed to the near band-edge emissions of the excitons bound to acceptors and of excitons bound to donors, respectively and that the peak at 3.24 eV was related to the donor-acceptor pair transitions. The activation energies of the excitons bound to neutral native donors, as obtained from the temperature-dependent PL spectra, were 10 and 85 meV, respectively.
Keywords: ORIENTATION; LAYER